PERBANDINGAN METODE FUZZY SUGENO DENGAN FUZZY TSUKAMOTO PADA SISTEM PREDIKSI HARGA SMARTPHONE BEKAS BERBASIS ANDROID DI WILAYAH MAKASSAR - Samuel Pinontoan; Izmy Alwiah Musdar; Hasniati (KHARISMA Tech, 2019)
This study aims to compare the Fuzzy Sugeno and Fuzzy Tsukamoto methods in the used android smartphone price prediction system based on Android in the Makassar region. The expected benefits of this research are as a service to get used Smartphone price information and pricing before the transaction. The theorems / methods used in this study are Fuzzy Sugeno and Fuzzy Tsukamoto. The research began by designing the Unified Modeling Language (UML). This program is tested using the Black Box Testing and testing method directly in the field. Based on the results of the study it can be concluded that the Fuzzy Sugeno method produces a better predictive value than the Fuzzy Tsukamoto method, with the MAPE value of 11.8% compared to 25.67%.